2013
DOI: 10.2310/jim.0b013e3182761264
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Osteopontin in the Assessment of Bone Mineral Density Status in Postmenopausal Women

Abstract: High levels of OPN in postmenopausal women are associated with low BMD, increased levels of bone turnover markers, and osteoporotic vertebral fractures. These findings suggest that OPN might play some role in the pathophysiology of postmenopausal osteoporosis and warrant further clinical investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 37 publications
(52 reference statements)
4
50
2
Order By: Relevance
“…In a word, OPN is a key regulator of RANKL-induced osteoclastogenesis under the condition of ovariectomy and unloading. Recent evidences from Korea [9], Romania [10], and Taiwan [11] indicate that high serum OPN levels are correlated with low BMD and increased bone turnover levels in Postmenopausal women. Based on above studies in rodents and humans, we speculated that OPN may be a pivotal element for bone mass changes in postmenopausal women in Southern China.…”
Section: Introductionmentioning
confidence: 99%
“…In a word, OPN is a key regulator of RANKL-induced osteoclastogenesis under the condition of ovariectomy and unloading. Recent evidences from Korea [9], Romania [10], and Taiwan [11] indicate that high serum OPN levels are correlated with low BMD and increased bone turnover levels in Postmenopausal women. Based on above studies in rodents and humans, we speculated that OPN may be a pivotal element for bone mass changes in postmenopausal women in Southern China.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that the osteopontin genetic polymorphisms can be used as a biomarker for the susceptibility and a predictor of clinical severity of spinal TB. Besides the roles in bone metabolisms, osteopontin also functions as a pro-inflammatory cytokine [37]. Osteopontin is found to regulate inflammatory responses of T and B cells, macrophages, and neutrophils [38].…”
Section: Discussionmentioning
confidence: 99%
“…OPN is one of the most abundant non-collagenous proteins in bone [21], originally isolated from bone, and is also found in the kidney, vascular and immune systems [22]. Hou et al reported that Serum OPN is related to LVH incidence in essential hypertension subjects by stimulating cardiomyocyte hypertrophy in vitro , but not OPN gene polymorphisms at -66T/G, -156G/GG, and and -443C/T [8].…”
Section: Discussionmentioning
confidence: 99%
“…In bones, OPN is produced by osteoblasts and osteoclasts, and involved in bone resorption and formation [24]. It has been suggested that OPN may facilitate the adhesion (or detachment) of the osteoclast to the bone surface and act as a signaling molecule or a scaffold in normal bone metabolism and turnover [22,25,26]. In human, high OPN levels have been indicated as a risk factor for low bone mineral density in postmenopausal women and used as a biomarker for early osteoporosis diagnosis [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation